Experimental study of the bending of the linter machine saw blade - Mukhammadiev Davlat; Ibragimov Farhod; Abzoirov Ortiq (E3S Web of Conferences, 2023)
The article presents the results of an experimental study of the bending of the saw blade of the 5LP linter machine. Therefore, a bench installation was made to conduct an experimental study of the process of the saw blade bending under contact with the ribs. At that, serial gaskets made of AK5M2 aluminum alloy and recommended gaskets of a new design made of St3 steel for the linter machine were used. When modeling the process of saw blades touching the ribs, a load with a bending force of 9.8, 19.6, 34.3 and 49 N is suspended on the maximum diameter of the saw blade. The research results showed that with an increase in bending forces from 9.8 to 49 N, the bending values of the saw blade with an aluminum gasket increase up to 4.5 mm, and with a steel gasket up to 3.5 mm. These results indicate the expediency of using a new design of steel gasket when assembling the saw cylinders of a linter machine, as it increases the bending stability of the saw blades by 28.6% compared to aluminum one AK5M2.